Treatment with Upadacitinib in Active Psoriatic Arthritis: Efficacy and Safety Data of the First 192 Patients from the UPJOINT Study, a Multicentre, Observational Study in Clinical Practice - Werner, Stephanie G.; Baraliakos, Xenofon; Reckert, Sabine; Bohl-Bühler, Martin; Laliberté, Marie Claude; Girard, Tanya; Jeromin, Katharina; Baschuk, Nikola; Fritz, Björn; Bessette, Louis; Hueber, Axel (Rheumatology and Therapy, 2023)
Introduction: Our aim was to investigate the efficacy and safety of upadacitinib (UPA) in patients with either oligo- or polyarticular active psoriatic arthritis (PsA) using routine clinical practice data from an observational, prospective, multicentre study. Methods: This interim analysis contains upadacitinib efficacy and safety data from the UPJOINT study, collected from baseline to the week 24 visit with a focus on composite measures, clinical assessments and patient-reported outcomes, amongst others, including minimal disease activity (MDA), very low disease activity (VLDA), Disease Activity Index for Psoriatic Arthritis (DAPSA), Leeds Enthesitis Index (LEI), resolution of dactylitis and nail psoriasis and body surface area affected by skin psoriasis (BSA). Results: A total of 296 patients with baseline data and 192 with completed week 24 visits were included in the analysis. The proportion of patients achieving MDA increased from 2.7% at baseline to 39.1% at week 24 (95% CI 32.1, 46.3). Similarly, the number of patients in DAPSA remission (DAPSA ≤ 4) increased from 0 at baseline to 32 (16.7%) by week 24. At that time, 59.4% of the patients were either in DAPSA remission or had low disease activity (DAPSA ≤ 14). During the 24 weeks time frame, the proportion of patients with BSA ≤ 3 increased from 80.7% to 91.1%. Furthermore, at weeks 12 and 24, 45.14% and 47.19% of affected patients showed a resolution of enthesitis. Active dactylitis and nail psoriasis at baseline were reported to affect 10.5% and 22.0%, decreasing to 2.6% and 5.7% at week 24, respectively. The safety findings are consistent with the known safety profile of upadacitinib in rheumatoid arthritis and PsA; no new safety risks were identified. Conclusion: The data from this study confirm the findings of previous randomized controlled trials suggesting UPA is an effective treatment for active PsA without any new safety signals in patients from daily clinical practice. Clinical Trial Registration: ClinicalTrials.gov identifier, NCT04758117.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Disease activity index for psoriatic arthritis; Efficacy; Minimal disease activity; Patient-reported outcomes; Psoriatic arthritis; Remission; Safety; Upadacitinib; Very low disease activity